Stress, strain, and structural dynamics : an interactive handbook of formulas, solutions, and MATLAB toolboxes - Yang, Bingen (Academic Press, 2022)
Stress, Strain, and Structural Dynamics: An Interactive Handbook of Formulas, Solutions, and MATLAB Toolboxes, Second Edition is the definitive reference to statics and dynamics of solids and structures, including mechanics of materials, structural mechanics, elasticity, rigid-body dynamics, vibrations, structural dynamics, and structural controls. The book integrates the development of fundamental theories, formulas, and mathematical models with user-friendly interactive computer programs that are written in MATLAB. This unique merger of technical reference and interactive computing provides instant solutions to a variety of engineering problems, and in-depth exploration of the physics of deformation, stress and motion by analysis, simulation, graphics, and animation.